Innovation Strategy Through E-Commerce Utilization in Increasing MSMEs in the Digital Era in the Niar Chips Business - Tahir, Sumiati; Wisudawaty, Ika; Pahrul (Cita konsultindo, 2025)
The development of digital technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to innovate in maintaining and increasing competitiveness. This study aims to explore innovation strategies through the use of e-commerce in improving the performance and market reach of MSMEs, with a case study on Niar's Kripik Business. The method used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation. The results of the study show that Niar Kripik has succeeded in utilizing e-commerce platforms such as Shopee, Tokopedia, and social media as a digital marketing strategy. Innovation is carried out through product repackaging, digitalization of promotions, and improving customer service. These findings reinforce the importance of technology adaptation in the sustainable development of MSMEs in the digital era.